Association Between Leadership and Job Satisfaction Of Primary Health Centers In Denpasar - Made Karma Maha Wirajaya (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Job satisfaction is very important because it can affect the behavior of employees working in the organization. Employees who are satisfied in the work will have positive behavior so they have a better performance. The preliminary study found that some employees are less satisfied with the supervisory aspects and attention of leader to employees. This study aims to determine the relationship between leadership and job satisfaction in primary health centers Denpasar. This research is a cross-sectional study, which involved75 samples. Samples were selected using total population sampling and analyzed using chi-square test. Most of the employees perceived a lack in the leadership of primary health centers leaders (52%) and satisfied with their work (52%). The result of chi-square test shows that leadership with OR = 12,01 (95% CI = 4,02-35,89) is related to job satisfaction of primary health centers in Denpasar. The leader who is able to feel employees need can make employees feel satisfied for the work. Employees who feel satisfied will give the best for the organization so can achieve its objectives. Most employees of primary health centers in Denpasar feel satisfied in work and leadership related to employees satisfaction in primary health centers in Denpasar.